Pengaruh Penggunaan Combine Harvester Terhadap Produktivitas - Dias Boy; Yossie Yumiati; Evi Andriani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Modern agriculture has experienced a significant transformation with the introduction of mechanization technology, one of which is the use of combine harvesters. This machine has a crucial role in increasing the efficiency and productivity of crop harvests, especially in the cultivation of cereal crops such as rice, wheat and corn. This research aims to determine the effect of using a combine harvester on lowland rice productivity. This research was carried out from September to October 2023 in Tanjung Alai Village. The data analysis used in this research is linear regression analysis to analyze the effect of yield loss due to the use of a Combine Harvester (CH) on productivity. The research results showed that the use of a Combine Harvester in Tanjung Alai Village, Mukomuko Regency was able to increase rice productivity by 487.56 kg/ha (11.21%) compared to harvesting without using a Combine Harvester. The T Test results show a significant value of 0.000, meaning that the significant value ˂ ɑ 0.05 indicates that the yield loss variable when harvesting using a Combine Harvester has a real or significant effect on rice productivity. Based on the regression equation formed, every 1% reduction in yield loss when harvesting using a Combine Harvester will increase rice productivity by 79,221 kg